Environmental practices of fruit growing companies in Mossoró, Rio Grande do Norte, Brazil - Chotten, Reinaldo; Pinto Filho, Jorge Luís de Oliveira (GOT: Revista de Geografia e Ordenamento do Território, 2025)
Research Purpose: This research aims to analyze the legal environmental practices of the fruit-growing sector in the municipality of Mossoró, Rio Grande do Norte, Brazil. Methodology: The study is based on bibliographic, documentary and field research, carried out in 14 companies, through the application of questionnaires on general aspects, environmental legality and environmental practices, and the data are treated in Microsoft Excel software. Findings: It was found that the profile of the analyzed companies is characterized by medium and large companies. It was evidenced that the companies have environmental licensing. It was also observed that technological innovation in companies’ processes contributed to improving efficiency, especially in the consumption of water, energy and waste management. Originality/Value: The study is original because it highlights corporate environmental management tools for the fruit production sector. https://doi.org/10.17127/got/2025.29.005